Niflumic Acid Reverses Airway Mucus Excess and Improves Survival in the Rat Model of Steroid-Induced Pneumocystis Pneumonia - Pérez, Francisco J.; Iturra, Pablo A.; Ponce, Carolina A.; Magne, Fabien; Garcia-Angulo, Víctor; Vargas, Sergio L. (Frontiers in Microbiology, 2019)
Although the role of adaptive immunity in fighting Pneumocystis infection is well known, the role of the innate, airway epithelium, responses remains largely unexplored. The concerted interaction of innate and adaptive responses is essential to successfully eradicate infection. Increased expression of goblet-cell-derived CLCA1 protein plus excess mucus in infant autopsy lungs and in murine models of primary Pneumocystis infection alert of innate immune system immunopathology associated to Pneumocystis infection. Nonetheless, whether blocking mucus-associated innate immune pathways decreases Pneumocystis-related immunopathology is unknown. Furthermore, current treatment of Pneumocystis pneumonia (PcP) relying on anti-Pneumocystis drugs plus steroids is not ideal because removes cellular immune responses against the fungal pathogen. In this study, we used the steroid-induced rat model of PcP to evaluate inflammation and mucus progression, and tested the effect of niflumic acid (NFA), a fenamate-type drug with potent CLCA1 blocker activity, in decreasing Pneumocystis-associated immunopathology. In this model, animals acquire Pneumocystis spontaneously and pneumonia develops owing to the steroids-induced immunodeficiency. Steroids led to decreased animal weight evidencing severe immunosuppression and to significant Pneumocystis-associated pulmonary edema as evidenced by wet-to-dry lung ratios that doubled those of uninfected animals. Inflammatory cuffing infiltrates were noticed first around lung blood vessels followed by bronchi, and both increased progressively. Similarly, airway epithelial and lumen mucus progressively increased. This occurred in parallel to increasing levels of MUC5AC and mCLCA3, the murine homolog of hCLCA1. Administration of NFA caused a significant decrease in total mucus, MUC5AC and mCLCA3 and also, in Pneumocystis-associated inflammation. Most relevant, NFA treatment improved survival at 8 weeks of steroids. Results suggest an important role of innate immune responses in immunopathology of steroid-induced PcP. They warrant evaluation of CLCA1 blockers as adjunctive therapy in this condition and describe a simple model to evaluate therapeutic interventions for steroid resistant mucus, a common condition in patients with chronic lung disease like asthma, chronic obstructive pulmonary disease (COPD) and cystic fibrosis.